Praça Nelson Mandela: onde o urbanismo, o design e a economia criativa se encontram - Silva Junior, Henrique Almeida (2021)
The speed with which cities and neighborhoods all around the world have guided reforms of large spaces and urban environments has consolidated a new intervention model in which other actors, once displaced from the process, now emerge and co-create in order to validate a thought more and more common and inherent to the modern times: the promotion of urban spaces and the resumption of environments where the human factor is the guiding thread of this process. The interdisciplinarity with which Design has re-signified its premises is much related to urban environments that promoted this culture from the umbrella and the precepts of the Creative Economy. In this way, the present paper aims to describe a constructive web about the construction of Nelson Mandela Square, in Botafogo, South Zone of the city of Rio de Janeiro, as well as to list in a holstic way this deeper look through Design and its processes that consolidate several examples around the world of spaces that had their territory deeply impacted and humanized. This project emerges from the relationship contained in the phenomenon undertaken in the construction of Nelson Mandela Square and the cultural and economic asset that follows the urban development of the neighborhood of Botafogo, which, is known as a “neighborhood of passage” and shows as a great core value the encounter of people Where the square is. Among the methodological possibilities approached, the case study stands out as one of the key procedures for understanding the problem and for the adequacy to the empirical phenomenon of the square as a meeting place. The result of this analysis contributes to illuminating the importance of Design as a discipline at the service of the city